Application Of The Family Deed Certificate On Blockchain For Data Security And Privacy - PO Abas Sunarya, Indri Handayani, AlfiahKhoirunisa, Sulistiawati, YudiSulaeman (International Journal of Advanced Science and Technology, 2020)
Technological developments have influenced various aspects of today’s people’s lives. The rapid development of technology causes a number of systems that have changed, especially in the era of Industrial Revolution 4.0 the use of new systems must bring enormous impact to society. Certificate of Family Deed is a family identity that contains data about the arrangement, relationships and number of family members. The family deed is an important thing to have for every citizen. However, the number of problems that occur because it is still using a conventional system that raises problems such as loss of family deed, and various manipulation of identity data. Thus, from this problem comes a solution to guarantee all data security and information that is blockchain technology. The blockchain technology is a transaction recording technology with modern technology, which can only be added but cannot be changed or removed. Blockchain technology can support various aspects of fields such as banking, education, health and especially for governance. This time the case is applied to the field of government, namely certificate of family deed on the blockchain, various problems in the event of the family deed that is the counterfeit of the many family members data and the editing of the change deed, it is very inflexible. With the certificate system of the family deed on the blockchain is to maintain the security of data so that the absence of data counterfeiting and minimize loss on the family deed. In this system use the literature method of review and how the blockchain works. Certificate of Family deed on blockchain is expected to bring a positive impact to the world of the digital era.